A seca no cotidiano: estudo dos efeitos da estiagem sobre famílias de comunidades rurais de Januária-MG - Gildarly Costa da Cruz (2018)
This dissertation aims to analyze the water management processes in the communities of Araçá and Onça located in the valley of the Peruaçu in gerais of the left margin of the Upper Middle São Francisco river in the North of Minas Gerais. For that, a qualitative field study was carried out, through interviews with semi structured itineraries, applied in the communities in two distinct periods: one at the end of the "dry season" and another in the "waters" period. Twenty-nine families were interviewed during the dry season and twelve families during the rainy season. In addition to the questionnaires applied to the families, four traditional connoisseurs were interviewed to describe the history of the place and the nature characteristics of the region. The results of this dissertation revealed that the natural sources of water of these two communities dried up the main sources of water for domestic consumption in 2017 and in the middle of 2018, were the community artesian tubular well and the cisterns of plates that collected rainwater. They were waters "produced" by public programs through external mediations: from Codevasf through the artesian well and the Peruaçu Project managed by Caritas Diocesan de Januária by means of plate cistern. The management of the main source of supply for the artesian well is local, that is, the community itself has created specific rules and articulations to deal with this source. The communities of Araçá and Onça revealed a situation of relative water scarcity and the importance of the measures taken to regulate the domestic supply, these measures are focused both for the conception of combat and for the coexistence with the drought. Certainly, the most relevant effect of years of acute droughts of environmental degradation and interventions of public programs was to establish in space a population that throughout history was fundamentally mobile taking advantage of the diverse sources of resources of the gerais; with the exhaustion of these resources the historical conditions of spatial mobility of the geralistas have ended.